Pengaruh Model Experiential Learning Berbantuan Team Quiz Terhadap Kemampuan Berpikir Kritis Siswa Kelas IV SD Negeri Gili Barat - Diah Mazroatul Arifah (LPPM Politeknik Pratama, 2023)
This study aims to determine the significant effect of the application of the quiz team-assisted experiential learning model on the critical thinking skills of fourth grade students at SD Negeri Gili Barat. This research is a quantitative research with the type of experimental research, the research design used is a quasi-experimental design, and the form of the design used is a nonequivalent control group design, meaning that neither the experimental nor control group samples were selected randomly. The sample used was 50 students from class IV SD Negeri Gili Barat. This study used experimental and control classes. Data collected using observation and tests of critical thinking skills. Trials of test instruments using validity tests, reliability tests, item difficulty levels, and item discriminating power. The data analysis used is the normality test and homogeneity test. The hypothesis test uses the independent sample t test. Based on the results of the independent sample t-test data analysis, the t-test obtained the result of tcount = 9,823 > ttable = 2.010, which means that Ho is rejected and Ha is accepted. So it can be concluded that there is a significant influence on the application of the quiz team-assisted experiential learning model on the critical thinking skills of class IV SD Negeri Gili Barat.